If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -1x = 13 Solving 29 + -1x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + -1x = 13 + -29 Combine like terms: 29 + -29 = 0 0 + -1x = 13 + -29 -1x = 13 + -29 Combine like terms: 13 + -29 = -16 -1x = -16 Divide each side by '-1'. x = 16 Simplifying x = 16
| r=-3 | | 17x-12=114+3x | | 5-7x=-15-3x | | -0.25y=16 | | x-2y+5=8 | | 8x^3+10x^2-5x-3=0 | | X+(-6)=9 | | -10p+9=12 | | 14c+35= | | 68-4*(3-1)3=c | | 6b+8= | | x^2+4bx+2b=0 | | X^3+2x^2-8x= | | 2x^12+3x= | | -3=5-t | | 173x+12=185 | | 173x+12=194 | | 173x+12=195 | | 3p-6= | | 173x+12=4278 | | 4b^2+7b+10=0 | | 4x^2-24x+100=0 | | 3q-40-4a=7a | | 3x+28=78 | | 3b-3=6(b+5) | | 4+b=-1 | | g+(-18)=-36 | | 3(8-3)6-1=p | | 16+t=-9 | | 13-4*n=11+2*n | | (3*5-5)(5-1)=x | | 4p-5=18 |